Alfa en omega : ’n studie in die trinitariese denke van Robert Jenson - Verhoef, Anne Hendrik (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DTh (Systematic Theology and Ecclesiology))—University of Stellenbosch, 2008.